Dislodgement effect of natural semiochemicals released by disturbed triatomines: a possible alternative monitoring tool - Manrique, Gabriel (2013)
The quick detection of domestic and peridomestic triatomines in their environments becomes difficult without the use of dislodgement substances that flush them out from their shelters. At present, tetramethrin 0.2% is being widely used in control programs. Although it is an efficient dislodging agent, its toxicity might affect the health of captured triatomines, of other insects and, to a lesser extent, of other animals, including humans. Here, we tested if semiochemicals released by disturbed adults of Triatoma infestans and/or Rhodnius prolixus can make larvae of the same species exit from their refuges. In a walking olfactometer we found that: 1) larvae of T. infestans were repelled by the odors released by disturbed adults of their own species and of R. prolixus, 2) larvae of R. prolixus did not change their behavior in the presence of odors released by adults of both species, and 3) activity levels were not modulated by these odors in any of both species. Besides, in pseudo-natural conditions we found an increased flushing-out activity of larvae of T. infestans when their shelters were sprayed with isobutyric acid or 3-pentanol, and of larvae of R. prolixus when sprayed with 3-methyl1butanol. We succeeded in this work to dislodge larvae of triatomines from artificial shelters using natural volatile compounds, allowing the capture of live bugs for further investigations (e.g., xenodiagnosis or genetic studies) and favoring ecological aspects (e.g., minimizing environmental insecticide-contamination and non-targeted mortality).